Utility of a Simplified Iliac Artery Calcium Scoring System to Guide Perioperative Management for Renal Transplantation - Werlin, Evan C.; Braun, Hillary J.; Walker, Joy P.; Freise, Jonathan E.; Amara, Dominic; Liu, Iris H.; Mello, Anna; Tavakol, Mehdi; Stock, Peter G.; Hiramoto, Jade S. (Frontiers in Medicine, 2021)
Non-contrast computed tomography scans of the abdomen and pelvis (CTAP) are often obtained prior to renal transplant to evaluate the iliac arteries and help guide surgical implantation. This study describes the association of iliac calcification scores with operative and clinical outcomes using a simplified scoring system. A retrospective review of 204 patients who underwent renal transplant from 1/2013-11/2014 and who had a CTAP within three years prior to transplant was performed. Common iliac artery (CIA) and external iliac artery (EIA) calcification on CTAP were assessed using a simple scoring system. Descriptive statistics, logistic regression, and survival analyses were performed. A total of 204 patients were included in the analysis. The mean age was 57.4 ± 11.2 years and 134/204 (66%) were men. Nineteen patients (9%) had a history of peripheral artery disease (PAD), 78 (38%) had coronary artery disease, and 22 (11%) had a previous cerebrovascular accident (CVA). Patients with severe right EIA plaque morphology were significantly more likely to require arterial reconstruction compared to those without severe plaque (3/14[21%] 4/153 [3%], p=0.03). Eleven patients (5%) had one or more amputations (toe, foot, or transtibial) following transplant. In UV logistic regression, severe EIA plaque morphology (OR 8.1, CI 2.2-29.6, p=0.002) and PAD (OR 10.7, CI 2.8-39.9, p=0.0004) were associated with increased odds of amputation. In the MV model containing both variables, EIA plaque morphology (OR 4.4, CI 0.99-18.3 p=0.04) and PAD (OR 6.3, CI 1.4-26.4, p=0.01) remained independently associated with increased odds of amputation. Over a median follow up of 3.3 years (IQR 2.9-3.6), 21 patients (10%) had post-operative major adverse cardiac events (MACE, defined as myocardial infarction, coronary intervention, or CVA), and 23 patients died (11%). In unadjusted Kaplan Meier analysis, CIA plaque (p=0.00081) and >75% CIA length calcification (p=0.0015) were significantly associated with MACE. Plaque burden in the EIA is associated with increased need for intra-operative arterial reconstruction and postoperative lower extremity amputations, while CIA plaque is associated with post-operative MACE. Assessment of CIA and EIA calcification scores on pre-transplant CT scans in high risk patients may guide operative strategy and perioperative management to improve clinical outcomes.